Using Mixed Methods to Understand Teaching and Learning in COVID 19 Times - Popa, Daniela; Repanovici, Angela; Lupu, Daciana; Norel, Mariana; Coman, Claudiu (MDPI AG, 2020)
This research focuses on teaching–learning behavior in the online environment under crisis conditions, such as those caused by COVID-19. Data were collected from 427 participants from Central and Eastern Europe and North and Central Asia. An integrative mixed method design was used, combining components of both qualitative and quantitative research. The research method used was the inquiry based on a semi-structured questionnaire, which combined closed items with open-ended and semi-structured interviews. The quantitative results revealed significant di erences between professors and students regarding the self-reported adaptability level, creativity, need for help in online teaching–learning, and collaboration with colleagues for solving problems in the online teaching–learning medium. The opinions of professors do not di er from those of students regarding the advantages, disadvantages, vulnerable areas, and aspects of online education. Thematic analysis, used to analyze the qualitative data, emphasized the participants’ perceptions of online teaching–learning e ciency in crises. Based on the results, it was concluded that the aspects that need to become a priority in online education concern mainly the didactic quality of the learning experience.